Exploratory Practice for Continuing Professional Development An Innovative Approach for Language Teachers - Slimani-Rolls, Assia; Kiely, Richard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'This volume makes an important contribution to our knowledge about how teachers can combine research and practice in addressing classroom issues. Case studies show in detail how individual teachers employ diverse methods to understand their students and "transform their classrooms", and provide us with rich insider accounts of teacher learning.' -Adrian Holliday, Professor of Applied Linguistics and Intercultural Education, University of Canterbury, UK This book explores the use of Exploratory Practice (EP) as a tool for Continuing Professional Development (CPD) by language teachers, and responds to the increasing demand for teachers to engage in research. It presents the results of a unique two-year longitudinal study that critically examines the implementation of EP by teachers of English and modern foreign languages. Through these case studies, the authors provide a critical account of EP as a form of practitioner research that bridges the divide between theory and practice. It emphasizes the centrality of teacher and learner learning in language education curriculum improvement, and gives a voice to teachers' perspectives on using EP in the classroom. This book will be of interest to language education professionals and scholars working in Applied Linguistics and Language Education. Assia Slimani-Rolls is Head of Research and Professional Development at the Institute of Languages and Culture, Regent's University London, UK. Richard Kiely is Director of Postgraduate Taught Programmes in Modern Languages and Linguistics at the University of Southampton, UK.
Part 1. Introduction -- Chapter 1. Exploratory Practice in language education: How teachers teach and learn; Richard Kiely and Assia Slimani-Rolls -- Chapter 2. Exploratory Practice as a principled framework for CPD; Assia Slimani-Rolls and Richard Kiely -- Chapter 3. Exploratory Practice and modern foreign languages in a globalised world; Assia Slimani-Rolls and Richard Kiely -- Part 2. Introduction -- Chapter 4. Teachers and researchers: Working towards a teacher learning community; Assia Slimani-Rolls and Richard Kiely -- Chapter 5. Using the mother tongue in the language classroom: Hindrance or help?; Michelle Rawson -- Chapter 6. Mobile phones in my language classroom: a cause for concern or a source for communication?; Maria Esther Lecumberri -- Chapter 7. A written feedback puzzle. Understanding 'local' pedagogy; Anna Costantino -- Chapter 8. Rebuilding practitioner self-efficacy through learner feedback; Chris Banister -- Chapter 9. Gaining deeper understanding of teaching speakingskills from collaborative inquiry; John Houghton -- Chapter 10. Insight into learner-generated materials; Marianna Goral -- Chapter 11. Opportunities and challenges for Exploratory Practice in the classroom; Assia Slimani-Rolls and Richard Kiely.
Keywords: Language and languages -- Study and teaching; Teachers -- Training of; Language Education; Language Teaching and Learning; Teaching and Teacher Education